Phisico-chemical and sensory characterization of frozen kiwi yogurt enriched with prebiotic (Research, Society and Development, 2021)
Frozen yogurt draws attention by taking advantage of the nutrients of yogurt and refreshing ice cream, in addition to being enriched with fruits that guarantee flavor, vitamins and antioxidant activity, as well as the addition of prebiotics, allowing greater functionality and the respective health benefits. Therefore, the objective of this work was to elaborate frozen kiwi flavored yogurt enriched with fructooligosaccharide. For this, the standard formulation (without prebiotic) F1 and F2 was developed with the addition of 5 and 10% of prebiotic, respectively. According to the physical-chemical analyzes, the parameters of pH, humidity, ash and proteins were the ones that suffered significant differences. The lipids, although not influenced by the amount of the prebiotic, were within the legislation. In the sensory analysis, the samples obtained an average above 7 for all sensory attributes, corresponding to “I liked it moderately” on the hedonic scale, demonstrating that the addition of the fructooligosaccharide did not negatively influence the characteristics of the product, being able to be a tasty and viable alternative for the use. of the functionality of fructooligosaccharide.